Integrating the prevention of mother-to-child transmission of HIV into primary healthcare services after AIDS denialism in South Africa: perspectives of experts and health care workers - a qualitative study - Jean Claude Mutabazi; Corie Gray; Lorrein Muhwava; Helen Trottier; Lisa Jayne Ware; Shane Norris; Katherine Murphy; Naomi Levitt; Christina Zarowsky (BMC Health Services Research, 2020)
Abstract Background Integrating Prevention of Mother-to-Child Transmission (PMTCT) programmes into routine health services under complex socio-political and health system conditions is a priority and a challenge. The successful rollout of PMTCT in sub-Saharan Africa has decreased Human Immunodeficiency Virus (HIV), reduced child mortality and improved maternal health. In South Africa, PMTCT is now integrated into existing primary health care (PHC) services and this experience could serve as a relevant example for integrating other programmes into comprehensive primary care. This study explored the perspectives of both experts or key informants and frontline health workers (FHCWs) in South Africa on PMTCT integration into PHC in the context of post-AIDS denialism using a Complex Adaptive Systems framework. Methods A total of 20 in-depth semi-structured interviews were conducted; 10 with experts including national and international health systems and HIV/PMTCT policy makers and researchers, and 10 FHCWs including clinic managers, nurses and midwives. All interviews were conducted in person, audio-recorded and transcribed. Three investigators collaborated in coding transcripts and used an iterative approach for thematic analysis. Results Experts and FHCWs agreed on the importance of integrated PMTCT services. Experts reported a slow and partial integration of PMTCT programmes into PHC following its initial rollout as a stand-alone programme in the aftermath of the AIDS denialism period. Experts and FHCWs diverged on the challenges associated with integration of PMTCT. Experts highlighted bureaucracy, HIV stigma and discrimination and a shortage of training for staff as major barriers to PMTCT integration. In comparison, FHCWs emphasized high workloads, staff turnover and infrastructural issues (e.g., lack of rooms, small spaces) as their main challenges to integration. Both experts and FHCWs suggested that working with community health workers, particularly in the post-partum period, helped to address cases of loss to follow-up of women and their babies and to improve linkages to polymerase-chain reaction (PCR) testing and immunisation. Conclusions Despite organised efforts in South Africa, experts and FHCWs reported multiple barriers for the full integration of PMTCT in PHC, especially postpartum. The results suggest opportunities to address operational challenges towards more integrated PMTCT and other health services in order to improve maternal and child health.